Arktiset kahvinystävät - Ulkuniemi, Seija (KUNSZT-kahvila, 2023)
Valokuvasarja Rovaniemellä asuvista/asuneista naisista. (Perustuu aiemmin esillä olleeseen kuvasarjaan, mutta nyt kuratoitu mukaan Euroopan kulttuuripääkaupungin InterUrban-tapahtumaan) COFFEE LOVERS FROM THE ARCTIC The background for this series goes back to year 2019 when I visited Santiago de Cuba. I drank coffee at the cozy Casa Dranguet which is dedicated to cherishing Cuban coffee culture. I was invited to have there an exhibition, and it occurred to me that coffee is a unifying factor in many ways between our different cultures. We Finns are called the coffee drinkers nation: we drink the most coffee per person in the world. In 2022, I showed in Casa Dranguet ten portraits of Finnish coffee drinkers under the title “Let´s make some coffee”. Historically, although Finns were subject to "tea-drink-Russia" in the 19th century (the Grand Duchy of Finland was an autonomous part of the Russian Empire in 1809-1917), coffee drinking became more common already then for several reasons: in a cold country, the warm coffee tasted good; it was contrary to liquor as a permitted stimulant; and its plot raised the social status of the people the custom dates to the nobility. Coffee has also been one of the few sensory pleasures that have been available to even the poor and that women have been allowed to enjoy. Since coffee was originally one of the few stimulants allowed for women, I focused on portraying women. Each of them introduced me to their favorite coffee cup, told me about its significance, and revealed their coffee drinking habits. Of course, we also had coffee together at the end of the shooting session! This series “Coffee lovers from the Arctic” brings portraits of nine coffee lovers from the Arctic with their coffee-related stories to Veszprém. All of them have either been born in Rovaniemi, the friendship city of Veszprém, or have lived there for many years. Most of them still live in Rovaniemi, the capital of Finnish Lapland.